2015
DOI: 10.1007/s10103-015-1800-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laser-assisted bleaching with Nd:YAG and diode lasers on shear bond strength of orthodontic brackets

Abstract: The aim of the present study was to assess the effect of laser-assisted bleaching with neodymium:yttrium-aluminum-garnet (Nd:YAG) and diode lasers on shear bond strength (SBS) of orthodontic brackets. One hundred and four extracted human premolars were randomly divided into four groups: group 1: No bleaching applied (control group); group 2: Teeth bleached with 40 % hydrogen peroxide; group 3: Teeth treated with 30 % hydrogen peroxide activated with Nd:YAG laser (1064 nm, 2.5 W, 25 Hz, pulse duration of 100 μs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…Mirhashemi et al compared the bond strength of a resin-based composite adhesive to enamel after bleaching with or without diode laser treatment and they found that diode laser reduced the bond strength of the resin onto bleached enamel surfaces. 36 This result was consistent with our findings. When the surface morphology of the diode laser group is evaluated that were observed with some debris, increased porosity, and enamel irregularities than the other groups.…”
Section: Discussionsupporting
confidence: 94%
“…Mirhashemi et al compared the bond strength of a resin-based composite adhesive to enamel after bleaching with or without diode laser treatment and they found that diode laser reduced the bond strength of the resin onto bleached enamel surfaces. 36 This result was consistent with our findings. When the surface morphology of the diode laser group is evaluated that were observed with some debris, increased porosity, and enamel irregularities than the other groups.…”
Section: Discussionsupporting
confidence: 94%
“…We believe that the internal bleaching process affects tooth structure more than the external bleaching process. Laser-assisted bleaching procedures can accelerate oxygen release and HP separation, with concomitant benefit to SBS 1 h after the bleaching process (38). However, Akin et al (39) reported lower SBS values in both the groups with Nd:YAG laser-assisted bleaching and bleaching without a laser.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the growing esthetic demands of patients, tooth bleaching has gained increasing popularity. [ 1 ] Although, in many cases, orthodontists need to bond the brackets to the bleached teeth,[ 2 ] a reduction in the bond strength to the bleached enamel has been reported. [ 3 ] In-office bleaching has advantages such as immediate effect and easier application and contribution to its higher concentrations of use than home bleaching.…”
Section: Introductionmentioning
confidence: 99%